Terapi Bermain Melalui Modifikasi Permainan Bola Sarung Sebagai Upaya Trauma Healing Anak-Anak Pasca Bencana - Dodi Irwansyah; Angger Widorotama; M. Anas Surimeirian (Program Studi Pendidikan Jasmani, Universitas Samudra, 2026)
Natural disasters cause long-term psychological trauma in children, posing significant risks of PTSD, anxiety, and depression. Post-disaster conditions in Manyak Payed, Aceh Tamiang Regency, are often faced with limited access to professional mental health services, necessitating innovative community-based psychosocial interventions. This Community Service (PKM) program aims to provide psychological support and trauma healing for children post-disaster through a play therapy approach using the modified traditional game of Bola Sarung, ensuring it is safe, fun, and culturally relevant. The implementation method involves socialization, game modification by training survivor cadres as facilitators, intervention implementation, assistance, evaluation, and program sustainability commitments targeting 30 affected children. The results show that effective coordination and socialization successfully enhanced community understanding. Furthermore, the implementation of the therapeutically modified Bola Sarung game demonstrated a positive impact by reducing anxiety levels and increasing joy as well as social interactions among children. The handover of supporting equipment to the village government also strengthens long-term independent program sustainability.